(untitled) (PJDOL, 2023)
This paper explores the learning styles and approaches of English language teachers enrolled in master’s program at an Open University in Pakistan. A total of 78 male and female teachers who were in their last stage of writing their dissertation at an open university in Pakistan were identified through stratified sampling and survey method was used to collect the data